USING THE DATABASE MANAGEMENT SYSTEM OF THE FINANCIAL STATEMENTS SUBMISSION - ALIN ISAC; CLAUDIA ISAC; ANCA JARMILA GUŢĂ (Annals of the University of Petrosani: Economics)
In administration, information technology represents a field with major implications in its functioning and the re-configuration of the computer infrastructure is responsible for a series of efficient changes concerning the development of the administrative process. Thus, our paper tries to determine the importance of Business to Government relation in increasing the flexibility of IT solutions used at the level of companies and especially in the financial accounting activity, starting from the necessity to implement the e-Government system in Romania. While revealing the company’s IT system and the financial accounting subsystem we also pointed out the stages of the accounting activities regarding the filling out of statistical reports such as fiscal declarations and annual financial statements.